2020
DOI: 10.1016/j.fss.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy clustering of fuzzy data based on robust loss functions and ordered weighted averaging

Abstract: In many real cases the data are not expressed in term of single values but are imprecise. In all these cases, standard clustering methods for single-valued data are unable to properly take into account the imprecise nature of the data. In this paper, by considering the Partitioning Around Medoids (PAM) approach in a fuzzy framework, we propose a fuzzy clustering method for imprecise data formalized in a fuzzy manner. In particular, in order to neutralize the negative effects of possible outlier fuzzy data in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 59 publications
(76 reference statements)
0
4
0
1
Order By: Relevance
“…Fuzzy clustering analysis is a method to discuss the quantitative classification of things from the perspective of fuzzy sets [6][7][8]. The fuzzy matrix is constructed according to the attributes of the research object itself, and the clustering relationship is determined according to a certain membership degree to classify the objective things [9].…”
Section: Fuzzy Clustering Analysismentioning
confidence: 99%
“…Fuzzy clustering analysis is a method to discuss the quantitative classification of things from the perspective of fuzzy sets [6][7][8]. The fuzzy matrix is constructed according to the attributes of the research object itself, and the clustering relationship is determined according to a certain membership degree to classify the objective things [9].…”
Section: Fuzzy Clustering Analysismentioning
confidence: 99%
“…Others are maximum and minimum method, arithmetic mean minimum method, geometric mean minimum method, absolute value index method and so on. Which one of the above methods is chosen depends on the characteristics of the actual problem [7].…”
Section: Fuzzy Clusteringmentioning
confidence: 99%
“…Since their debut in 1965, FSs have been applied in a variety of contexts and fields. Artificial intelligence [15], medicine [16], statistics [17], medical diagnosis [18,19], and clustering [20,21] are a few fields in which FSs are used. Some researchers proposed aggregation operators (AOs), such as Fahmi et al [22], who suggested cubic fuzzy Einstein AOs and their use in DM issues.…”
Section: Introductionmentioning
confidence: 99%